Engineering Quality Feelings : Applications in products, service environments and work systems - Ayas, Ebru (KTH, Ergonomi, 2011)
Contemporary quality issues in product design are moving from materialistic to emotional user fulfillment; comprehensive research is needed to examine quality product feelings. This research is directed toward a deeper understanding of user and customer quality feelings for different product types, including services. The quality feelings concept includes dimensions of product quality, especially functionality, ergonomics and aesthetics. The first objective of this thesis is to identify, prioritize and synthesize quality feelings into product attributes in product development applications. The second objective is to explore, test and propose methodological approaches for designing quality feelings into products. Several methods from psychology, ergonomics, statistics and probabilistic methods and heuristics were applied to achieve the objectives. From a methodological viewpoint, Likert scales, free elicitation technique and Just About Right scales were applied for data collection. Multiple Regression, Factor Analysis, Correspondence Analysis, Genetic algorithms, Partial Least Squares (PLS) and Rough Sets (RS) were applied for data analyses. For ergonomic product evaluations, direct observations, 3D workload simulations, time and frequency analyses were conducted. Five product applications are included in this thesis: operator driver cabin design of reach trucks, steering wheel design trigger switch design in right-angled nutrunners, bed-making systemsproducts and waiting room environments. Heuristic methods were found effective when there is a high number of product attributes that interact to provide quality feelings. RS results are consistent with PLS attribute predictions. When the number of product attributes is large in comparison to the number of observations, PLS extracts informative results for quality feelings. The RS method is effective in identifying interactions among design attributes. Quality feelings are associated with both tangible (tactile characteristics) and intangible (quick and easy to use) product characteristics. Words such as safety, functionality, ergonomics, comfort, reliability, supportiveness, usability, feedback, pleasantness, attractiveness, durability and distinctiveness describe quality feelings from tangible products and services. Based on product type, the quality dimensions represented by these words possess different interactions and dependencies. In work environments, products act as prostheses between workers for social interaction, which need to be considered as important quality feelings dimensions. === QC 20111017